Docosahexaenoic acid (DHA) prevents corticosterone‐induced changes in astrocyte morphology and function. Issue 6 (29th January 2016) - Champeil‐Potokar, Gaëlle; Hennebelle, Marie; Latour, Alizée; Vancassel, Sylvie; Denis, Isabelle
Abstract: The many functions of astrocytes, such as glutamate recycling and morphological plasticity, enable them to stabilize synapses environment and protect neurons. Little is known about how they adapt to glucocorticoid‐induced stress, and even less about the influence of dietary factors. We previously showed that omega‐3 polyunsaturated fatty acids (ω3PUFA), dietary fats which alleviate stress responses, influence the way astroglia regulate glutamatergic synapses. We have explored the role of docosahexaenoic acid (DHA), the main ω3PUFA, in the astroglial responses to corticosterone, the main stress hormone in rodents to determine whether ω3PUFA help astrocytes resist stress. Cultured rat astrocytes were enriched in DHA or arachidonic acid (AA, the main ω6PUFA) and given 100 nM corticosterone for several days. Corticosterone stimulated astrocyte glutamate recycling by increasing glutamate uptake and glutamine synthetase (GS), and altered the astrocyte cytoskeleton. DHA‐enriched astrocytes no longer responded to the action of corticosterone on glutamate uptake, had decreased GS, and the cytoskeletal effect of corticosterone was delayed, while AA‐enriched cells were unaffected. The DHA‐dependent anti‐corticosterone effect was related to fewer glucocorticoid receptors, while corticosterone increased DHA incorporation into astrocyte membranes. Thus, DHA helps astrocytes resist the influence of corticosterone, so perhaps promoting a sustainable response by the stressed brain. We show that corticosterone increases the glutamate recycling capacity of rat cortical astrocytes in culture, and alters their morphology, which may be detrimental in the long term. Increasing the membrane incorporation of docosahexaenoic acid (DHA), the main omega‐3 in brain, reduces the amount of glucocorticoid receptors (GR) and prevents the effects of corticosterone. This may help the astrocytes maintain a functional phenotype in chronic stress situations. Abstract : We show that corticosterone increases the glutamate recycling capacity of rat cortical astrocytes in culture, and alters their morphology, which may be detrimental in the long term. Increasing the membrane incorporation of docosahexaenoic acid (DHA), the main omega‐3 in brain, reduces the amount of glucocorticoid receptors (GR) and prevents the effects of corticosterone. This may help the astrocytes maintain a functional phenotype in chronic stress situations.